PENYESUAIAN DIRI ORANGTUA ANAK PENGIDAP KANKER DALAM PROSES PENGOBATAN ANAK: STUDI DI YAYASAN RUMAH CINTA ANAK KANKER BANDUNG - Kasnia Alfiani Pratiwi Lempang; Lina Favourita Sutiaputri; Diana Diana (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2021)
The research aims to describe more about the adjustment by the parents of children with cancer to the child’s treatment process at Rumah Cinta Anak Kanker Bandung Foundation wich includes the characteristic of informants, absence of excessive emotionally, absence of psychological mechanism, absence of the sense of personal frustration, rational deliberation and self-directon, ability to learn and utilization of past experiences, and realistic, objective attitude. The research uses a qualitative approach with descriptive methods. The informants is determined by using purposive sampling to five informants consisting of the parents of children with cancer as main care giver, two the parents of children with cancer as companion of main care giver, and Coordinator of the parents of children with cancer at Rumah Cinta Anak Kanker Foundation. Data collection uses an indepth interview, observation, and documentation study. The result shows that the adjustment by the parents of children with cancer has been done well, but there are difficulties to control excessive emotions and have dificulty being realistic and objective. The parents of children with cancer have excessive anxiety about the child’s health condition while accompanying the child’s treatment process. Based on this problems, the reseacrchers proposes a program to reduce anxiety about child’s health condition of the parents through nourishment therapy and reality therapy.